ERBB2 (HER2) amplifications and co-occurring KRAS alterations in the circulating cell-free DNA of pancreatic ductal adenocarcinoma patients and response to HER2 inhibition - Barzi, Afsaneh; Weipert, Caroline M.; Espenschied, Carin R.; Raymond, Victoria M.; Wang-Gillam, Andrea; Nezami, Mohammad Amin; Gordon, Eva J.; Mahadevan, Daruka; Mody, Kabir (Frontiers in Oncology, 2024)
Purpose: Despite accumulating data regarding the genomic landscape of pancreatic ductal adenocarcinoma (PDAC), olaparib is the only biomarker-driven FDA-approved targeted therapy with a PDAC-specific approval. Treating ERBB2(HER2)-amplified PDAC with anti-HER2 therapy has been reported with mixed results. Most pancreatic adenocarcinomas have KRAS alterations, which have been shown to be a marker of resistance to HER2-targeted therapies in other malignancies, though the impact of these alterations in pancreatic cancer is unknown. We describe two cases of ERBB2-amplified pancreatic cancer patients treated with anti-HER2 therapy and provide data on the frequency of ERBB2 amplifications and KRAS alterations identified by clinical circulating cell-free DNA testing. Methods: De-identified molecular test results for all patients with pancreatic cancer who received clinical cell-free circulating DNA analysis (Guardant360) between 06/2014 and 01/2018 were analyzed. Cell-free circulating DNA analysis included next generation sequencing of up to 73 genes, including select small insertion/deletions, copy number amplifications, and fusions. Results: Of 1,791 patients with pancreatic adenocarcinoma, 36 (2.0%) had an ERBB2 amplification, 26 (72.2%) of whom had a KRAS alteration. Treatment data were available for seven patients. Two were treated with anti-HER2 therapy after their cell-free circulating DNA result, with both benefiting from therapy, including one with a durable response to trastuzumab and no KRAS alteration detected until progression. Conclusion: Our case series illustrates that certain patients with ERBB2-amplified pancreatic adenocarcinoma may respond to anti-HER2 therapy and gain several months of prolonged survival. Our data suggests KRAS mutations as a possible mechanism of primary and acquired resistance to anti-HER2 therapy in pancreatic cancer. Additional studies are needed to clarify the role of KRAS in resistance to anti-HER2 therapy.